2019
DOI: 10.1111/jace.16863
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition behavior of Pb(Hf, Sn, Ti, Nb)O3 ceramics at morphotropic phase boundary

Abstract: The phase transition and dielectric properties of Pb0.988(Hf0.945SnxTi0.03‐xNb0.025)O3 ceramics (0 ≤ x ≤ 0.03, correspondingly abbreviated as H1, H2, H3, and H4) at the morphotropic phase boundary were systematically investigated. X‐ray diffraction results and P‐E hysteresis loops show that the dominate orthorhombic antiferroelectric phase and a small amount of the tetragonal FE phase coexist in Pb0.988(Hf0.945SnxTi0.03‐xNb0.025)O3 ceramics. As the Sn content increases, the antiferroelectricity is significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…and/or B-site doping (Sn 4+ , Ti 4+ , Nb 5+ , etc. ), and is classified roughly into two categories, namely double and multiple hysteresis loops, respectively, in terms of reversible phase transitions. , The two kinds of P–E loops exhibit remarkable differences in the energy-storage performance. As can be seen in Figure a,b, those compositions (circled ones) with multiple hysteresis loops always have superior energy-storage performance to the compositions exhibiting double hysteresis loops (uncircled ones).…”
Section: Introductionmentioning
confidence: 99%
“…and/or B-site doping (Sn 4+ , Ti 4+ , Nb 5+ , etc. ), and is classified roughly into two categories, namely double and multiple hysteresis loops, respectively, in terms of reversible phase transitions. , The two kinds of P–E loops exhibit remarkable differences in the energy-storage performance. As can be seen in Figure a,b, those compositions (circled ones) with multiple hysteresis loops always have superior energy-storage performance to the compositions exhibiting double hysteresis loops (uncircled ones).…”
Section: Introductionmentioning
confidence: 99%
“…23 Yang et al investigated the phase transition and dielectric properties of Pb 0.988 (Hf 0.945 Sn x Ti 0.03−x Nb 0.025 )O 3 ceramics (0 ≤ x ≤ 0.03) at the morphotropic phase boundary (MPB) and found the Sn content enhanced the antiferroelectricity. 24 Ge et al fabricated PbHf 1−x Sn x O 3 (PHS) AFE ceramics, and the double P-E loop was modified via the variation of Sn content. In the composition with x = 0.07, a high recoverable energy storage density of 10.2 ± 0.4 J/cm 3 with a high energy efficiency of 78.9% is achieved at 320 kV/cm.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al. investigated the phase transition and dielectric properties of Pb 0.988 (Hf 0.945 Sn x Ti 0.03− x Nb 0.025 )O 3 ceramics (0 ≤ x ≤ 0.03) at the morphotropic phase boundary (MPB) and found the Sn content enhanced the antiferroelectricity 24 . Ge et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that PbHfO 3 single crystal undergoes two structural transformations in broad frequency and temperature range: at about 163°C from the antiferroelectric (AFE1) to another intermediate antiferroelectric phase (AFE2) and at about 209°C from the AFE2 to the paraelectric (PE) phase [5, 12]. For more profound research, researchers are usually doping different ions to improve the dielectric properties of PbHfO 3 , such as Ti‐doped PbHfO 3 antiferroelectric crystals [13], (1− x )PbSc 0.5 Ta 0.5 O 3 –( x )PbHfO 3 ceramics [14], PbHfO 3 –BaHfO 3 and PbHfO 3 –SrHfO 3 [15] and so on. In comparison with PbHfO 3 single crystal, phase‐transition temperatures of PbHf 1− x Sn x O 3 (PSH, with x = 0.025) single crystal showed a slight decrease and reached about 153 and 201°C, respectively, for AFE1 to AFE2 phase and AFE2 to PE phase [5].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the excellent characteristics of PSH single crystal, we conducted PSH ceramics as our research. In previous work, both Ti‐doped [13] and Sn‐doped [6] PbHfO 3 crystals show excellent FE and antiferroelectric properties due to Sn or Ti doping plays a crucial role in changing properties of PbHfO 3 , especially in structural phase transitions. Fan et al reported a new cloverleaf AFE domain structure in PbHfO 3 ceramics.…”
Section: Introductionmentioning
confidence: 99%